2016
DOI: 10.1016/j.jcm.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between the Effects of Passive and Active Soft Tissue Therapies on Latent Trigger Points of Upper Trapezius Muscle in Women: Single-Blind, Randomized Clinical Trial

Abstract: Both passive and active soft tissue therapies were determined to reduce pain intensity and increase ACLF range of motion, although passive therapy was more effective in increasing PPT in these patients compared with the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…Kumaresan et al also reported a significant decrease in pain and an increase in ROM after 7 treatment sessions with PRT (27). trast to the present study, PPT improvement was statistically significant in the mentioned research (18). In another study, Mohammadi Kojidi investigated the effects of PRT on the latent MTrPs of upper trapezius among computer users.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Kumaresan et al also reported a significant decrease in pain and an increase in ROM after 7 treatment sessions with PRT (27). trast to the present study, PPT improvement was statistically significant in the mentioned research (18). In another study, Mohammadi Kojidi investigated the effects of PRT on the latent MTrPs of upper trapezius among computer users.…”
Section: Discussionsupporting
confidence: 44%
“…In each session, the order of assessment was randomlay determined, using a table of random numbers. The follow-up was performed 10 days after the first session (1 week after the third session) (18,21).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Among the manual treatment of TrPs several techniques have been proposed that act directly or indirectly on the TrPs. Techniques that are thought to reduce the muscle contraction with mechanical forces (compression, distraction) acting directly on the TrPs site or the surrounding tissues are ischemic compression ( 45 ), myofascial release ( 46 ), acupressure ( 47 ), and specific soft tissues mobilization techniques ( 48 ). Indirect techniques, such as muscle energy ( 49 ), positional release ( 50 ), and strain–counterstrain techniques ( 51 ) are thought to reduce muscle contraction for neurophysiological mechanisms regulating the muscle tone.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, interventions into fascia structures would seem fairly appropriate, supporting the healing process of many orthopaedic or neurological conditions. Some scientific reports suggest that the proper manual stimulation may provide positive modelling of fascia structures in pathological conditions [34][35][36][37][38][39][40][41].…”
Section: Mini Reviewmentioning
confidence: 99%